PRAGMATIC INTERPRETATIONS OF METAPHYSICAL PROBLEMS (WILLIAM JAMES) - Nataliia Salnikova ("Scientific Information Agency "Science-technologies-information" LLC, 2019)
The main task of philosophy W. James considered on the study of problems of metaphysics, theology and morality. In this connection, the concept of "truth" and the problem of its essence occupy one of the leading places in the concept of pragmatism. In general, James believed that the practical consequences and results of metaphysical concepts and religious teachings are shaped by the spiritual ideas of their followers. James's concept of pragmatism does not contain any new arguments in favor of the solution of philosophical problems in accordance with logic and common sense, but there are reasons for such a decision to be considered necessary. This is due to the interrelation of metaphysical ideas with the solution of practically important problems.